The politics of labour relations in global production networks: Collective action, industrial parks, and local conflict in the Ethiopian apparel sector. (October 2021) - Oya, Carlos; Schaefer, Florian
Highlights: We analyse the dynamics of labour relations in new manufacturing locations serving global production networks. The new export-oriented apparel sector in Ethiopia has already seen both collective and individual resistance from workers. There are various manifestations of formal and informal resistance from wildcat strikes, to absenteeism and high turnover. Industrial strife reflects an interplay of sectoral pressures, factory-based grievances, and anti-government protests. Abstract: In this paper we examine the emerging politics of labour agency as new manufacturing locations are incorporated into existing global production networks, using the example of the Ethiopian apparel industry. The Ethiopian state has employed an active space-based industrial policy to attract leading apparel manufacturers into a series of new industrial parks in the country. Both investors and the Ethiopian government expected to find a large and pliant labour force willing to work for low wages. However, the new sector has already seen a wave of collective and individual resistance from workers. We ask which factors contribute to drive and constrain labour agency and shape the specific forms it takes in firms tied into leading global production networks. Drawing on a large-N quantitative survey of factory workers and in-depth qualitative interviews with managers, workers, trade union representatives and government officials, we show how the quality of industrial relations depends not just on state action and the business strategies of lead firms in production networks, but also on variegated forms of labour agency used both by organised and unorganised Ethiopian workers. We find that many industrial conflicts result from the collision of the productivity imperatives of manufacturing firms tied into demanding, but low value-added, segments of global production networks with the expectations of workers with limited prior experience in industrial jobs, but are compounded by the contradictory actions of different state agencies, a lack of formal unionisation, and the contingent interactions of factory based grievances with local political conflicts. Industrial parks emerge as spaces of particular contestation. Our findings highlight the need to adopt an understanding of labour regimes grounded in local political realities. These findings have implications for the design of industrial policies and labour market institutions aiming to support firms and workers in emerging manufacturing clusters.